THE ROLE OF FOMO (FEAR OF MISSING OUT) IN IMPROVING CONSUMER PERSPECTIVES FOR SKINTIFIC PURCHASE DECISIONS ON THE TIKTOK APPLICATION IN THE SURABAYA AREA - Hardiana Putri, Nisa Aulia; Is Fadhilah (Pedagogic Research-Applied Literacy Journal, 2025)
This study examines the role of Fear of Missing Out (FOMO) in influencing customer perspectives and purchasing decisions for Skintific products on Tik Tok in Surabaya. Using a descriptive qualitative method, data was collected through interviews, observation, and documentation with eight customers and two sellers. The findings reveal that FOMO drives customers to make quick and impulsive purchases due to promotions, influencer reviews, and user testimonials. Tik Tok algorithm enhances this urgency by frequently showing trending content. The study concludes that FOMO is an effective digital marketing strategy that boosts consumer engagement, brand awareness, and loyalty in the beauty industry.